Dialektolodzy na manowcach. O wpływie niemczyzny na gwary Warmii i Mazur - Sobolewska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The article contains a critical analysis of the opinions of dialectologists studying the dialects of Warmia and Masuria. In their view, firmly established since the 1960s, the influence of the German language on the regions’ dialects was insignificant and superficial. The article recalls and studies the sources used in the compilation of Słownik gwar Ostródzkiego, Warmii i Mazur, presents the linguistic material published therein. It poses a thesis that, although the language system of the studied dialect is Polish, the naming system comprising all fundamental spheres of life was shaped under a significant and versatile influence of German. Loanwords, semantic borrowings, replicas from the German language enter into numerous relationships of synonymy, hyponymy antonymy or hyperonymy with Polish words, creating complex and cohesive semantic fields within which the users of a dialect moved freely.